2018
DOI: 10.1371/journal.pone.0191097
|View full text |Cite
|
Sign up to set email alerts
|

A new strength assessment to evaluate the association between muscle weakness and gait pathology in children with cerebral palsy

Abstract: AimThe main goal of this validation study was to evaluate whether lower limb muscle weakness and plantar flexor rate of force development (RFD) related to altered gait parameters in children with cerebral palsy (CP), when weakness was assessed with maximal voluntary isometric contractions (MVICs) in a gait related test position. As a subgoal, we analyzed intra- and intertester reliability of this new strength measurement method.MethodsPart 1 –Intra- and intertester reliability were determined with the intra-cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
44
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(49 citation statements)
references
References 55 publications
4
44
0
1
Order By: Relevance
“…Therefore, it is important to quantitatively measure the motor function in this population [9,10]. Furthermore, muscle strength was reported to be a major factor that influences gait [16][17][18]. Wang et al, reported that in patients with spastic cerebral palsy, FTSST findings correlated not only with the strengths of the primary lower extremity extensors, but also with the strengths of the trunk extensors, hip flexors, hip abductors, knee flexors, and ankle dorsiflexors [9].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is important to quantitatively measure the motor function in this population [9,10]. Furthermore, muscle strength was reported to be a major factor that influences gait [16][17][18]. Wang et al, reported that in patients with spastic cerebral palsy, FTSST findings correlated not only with the strengths of the primary lower extremity extensors, but also with the strengths of the trunk extensors, hip flexors, hip abductors, knee flexors, and ankle dorsiflexors [9].…”
Section: Discussionmentioning
confidence: 99%
“…Synergies weights were scaled in such a way that one represented the maximal weight of a muscle to a synergy. Then, the number of synergies for average value of N90 were grouped with k-means cluster analysis and the average synergy weights and activations of 10 steps for each child was calculated.The maximal force (N) from the MVIC of three representative trials for each muscle group was averaged and net joint torques normalized to bodyweight (Nm�kg -1 ) were calculated by multiplying the average maximal force with the moment arm (which was standardized at 75% of the segment length) and dividing by the body weight of the child [35].…”
Section: Discussionmentioning
confidence: 99%
“…To decrease compensatory mechanisms and influence of the assessor on MVIC-outcomes, we used a custom-made chair in which the participants were secured with straps around the pelvis and upper legs, and the HHD was fixed to the chair. We placed the HHD at 75% of the segment length (Figure 1 ) and applied a gravity correction for those MVICs where gravity influenced the output data (KF MVIC and PF MVIC), by subtracting the gravitational torque in rest position from the MVIC-outcomes (Boiteau et al, 1995 ; Goudriaan et al, 2018 ). The children first performed one test trial, followed by three actual MVICs, with a duration between 3 and 5 s. Between each trial, the children rested at least 10 s, and between each muscle group, they had a resting period of at least 2 min.…”
Section: Methodsmentioning
confidence: 99%
“…Walking speed (in m/s) was extracted from the gait data for each child and converted to a non-dimensional value with the formula of Hof ( 1996 ) to determine whether differences in walking speed could explain potential differences in tVAF 1 between the three groups (Ivanenko, 2005 ; Shuman et al, 2016a ). Force data (in Newtons) from the MVICs was resampled to 100 Hz and the average maximal force out of three trials was calculated (Willemse et al, 2013 ; Goudriaan et al, 2018 ). Subsequently, the net joint torque normalized to bodyweight (Nm/kg) was determined for all MVICs for each participant (Supplementary Tables 1 – 3 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation